Complex vascular anomalies and tissue overgrowth of limbs associated with increased skin temperature and peripheral venous dilatation: parks weber syndrome or PROS? - Li Xin Su; Yi Sun; Zhenfeng Wang; Deming Wang; Xitao Yang; Lianzhou Zheng; Mingzhe Wen; Xindong Fan; Ren Cai (Hereditas, 2022)
Abstract PIK3CA-related overgrowth spectrum (PROS) is a series of congenital, sporadic disorders that are associated with segmental overgrowth phenotypes and postzygotic, somatic gene mutations in the PIK3CA-ATK-mTOR pathway. The variability and overlapping phenotypes between PROS and other complex vascular malformations make the differential diagnosis confusing and challenging. PROS should be considered for the differential diagnosis with other complex vascular malformations and syndromes with a tissue overgrowth phenotype, such as Parkes-Weber syndrome (PWS). Herein, we diagnosed one unique clinically challenging case manifested as capillary malformation (CM), limb overgrowth, as well as increased skin temperature and peripheral venous dilatation of lower limb that indicated a potential fast-flow lesion. The patient was initially diagnosed with PWS. Contrary to the previous diagnosis, based on further MR imaging and digital subtraction angiography (DSA), which ruled out the existence of AVMs and AVFs, and molecular analysis with targeted next-generation sequencing (NGS) revealing a somatic PIK3CA mutation, we ultimately diagnosed that the patient had a unique form of PROS simulating PWS phenotypes. We suggest that it is important to propose the differential diagnosis of PWS and PROS, two diseases that share a common overgrowth phenotype. We recommended radiological diagnosis such as MRI, CT and DSA as well as further molecular diagnosis to provide more information for the assessment of vascular lesions and to further guide clinical treatment strategies.